Review: Eustathii Antiocheni, Patris Nicaeni, Opera quae Supersunt Omnia - Ward, Robin (The journal of theological studies, 2005)
Eustathii Antiocheni, Patris Nicaeni, Opera quae Supersunt Omnia José H. Declerck cccclxii + 286 (Corpus Christianorum Series Graeca, 51.)Turnhout Brepols Leuven Leuven University Press 2002 2 503 40511 8 €345